2018
DOI: 10.22214/ijraset.2018.2056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Different Classification Algorithms on ILPD Dataset to Predict Liver Disorder

Abstract: Data mining techniques can be applied in various fields such as Information Retrieval, Business analytics, Medicine and many more. This paper deals with medical field which mainly focuses on liver disease diagnoses. The aim of this study is to implement different classification algorithms on Indian Liver Patient Dataset (ILPD) using WEKA in order to get proper prediction of liver disorders. Feature selection is carried out on the dataset. Pre-processing is carried out to pre-process and cluster the data. K mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In terms of the analysis methods, we used both new and traditional supervised analysis methods, such as machine learning algorithms and multivariate regression methods, to predict the childhood outcomes of ARI disease symptoms. Furthermore, these findings complement other comparative machine learning findings [38][39][40][41] in providing evidence of the better performance of the random forest algorithm (88.7%) than traditional methods of analysis. However, other studies [42,43] contradicted these findings.…”
Section: Discussionsupporting
confidence: 81%
“…In terms of the analysis methods, we used both new and traditional supervised analysis methods, such as machine learning algorithms and multivariate regression methods, to predict the childhood outcomes of ARI disease symptoms. Furthermore, these findings complement other comparative machine learning findings [38][39][40][41] in providing evidence of the better performance of the random forest algorithm (88.7%) than traditional methods of analysis. However, other studies [42,43] contradicted these findings.…”
Section: Discussionsupporting
confidence: 81%
“…A comparative study conducted for predicting the effective diagnosis of liver diseases using comparisons of methods such as Neural Network, Support Vector Machine, Random Forest, and Decision Tree, revealed that the Neural Network and Random Forest methods achieved the highest accuracy rate [31]. Another study carried out for predicting liver disorders showed that the Random Forest algorithm also performed well compared to the other methods employed in the study [32]. A study conducted by Marikani and Shyamala (2017) using clinical and demographic data revealed that RF (Accuracy = 96.3%) performed better in predicting heart disease [33], also similar to the Mani et al (2012) study conducted using Demographic and clinical test results in predicting type 2 diabetes [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Multilayer Perceptron can be further used to diagnose the liver disorder efficiently. Another concept for diagnoses of liver disease was proposed by Pathan et al (2018). Various classification algorithms were used such as Naïve Bayes, Adaptive Boosting (Ada Boost), J48, Bagging and Random Forest.…”
Section: Literature Reviewmentioning
confidence: 99%